A lectin with antifungal activity from the mussel Crenomytilus grayanus. Issue 2 (February 2015) - Chikalovets, Irina V.; Chernikov, Oleg V.; Pivkin, Mikhail V.; Molchanova, Valentina I.; Litovchenko, Alina P.; Li, Wei; Lukyanov, Pavel A.
Abstract Lectins (carbohydrate-binding proteins) are well known to actively participate in the defense functions of vertebrates and invertebrates where they play an important role in the recognition of foreign particles. In this study, we investigated of in vitro antifungal activity of lectin from the mussel Crenomytilus grayanus (CGL). Enzyme-linked immunosorbent assay indicated that CGL was predominantly detectable in tissues of mantle and to a lesser degree in the tissues of muscle, hepatopancreas, gill and hemocytes. After challenged by Pichia pastoris the level of CGL was upregulated and reached the maximum level at 12 h post challenge and recovered to the original level at 24 h. The lectin was capable of inhibiting the germination of spores and hyphal growth in the fungi. All these results indicated that CGL is involved in the innate immune response in mollusc animals.